Pemberdayaan Kelompok Lembaga Pengelola Hutan Desa Terhadap Agro-Ekowisata di Desa Pasar Rawa Kecamatan Gebang Kabupaten Langkat - Has, Dini Hadiani; Putra, Hendris Syah; Sari, Ratna (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2025)
Pasar Rawa Village has diverse natural potential, namely horticulture, fisheries to tourism, especially mangrove forests that promise as tourist destinations. Potential needs to be identified in depth to determine sustainable agroecotourism development. The problem in managing the potential of mangrove tourism is the management, involvement and support of local communities. The purpose of Community Service activities is to provide understanding, knowledge, about agroecotourism and the management and development of agroecotourism in Pasar Rawa Village. The methods carried out are field surveys, socialization, training using refractometers and mangrove planting. The socialization activity was carried out with participants being members of the LPHD group totaling 27 people. In the socialization presentation, the community was very enthusiastic in exploring the existing potentials such as local culture and typical food of the region. Training on the use of refractometers was carried out so that group members could find out the exact value of the sweetness in melons that could be sold and used as an attraction for tourists to try melons that have a unique taste so that they became the selling point of ecotourism and agro-tourism. One of the conservation efforts is mangrove planting.            Keywords: agro-ecotourism; community empowerment; mangrove forest  Abstrak: Desa Pasar Rawa memiliki potensi alam beragam, yaitu hortikultura, perikanan hingga pariwisata, terutama hutan mangrove menjanjikan sebagai destinasi wisata. Potensi perlu diidentifikasi secara mendalam untuk menentukan pengembangan agroekowisata berkelanjutan. Permasalahan dalam mengelola potensi wisata mangrove yaitu pengelolaan, keterlibatan dan dukungan masyarakat lokal. Tujuan kegiatan Pengabdian kepada Masyarakat adalah untuk memberikan pemahaman, pengetahuan, tentang agroekowisata dan pengelolaan serta pengembangan menjadi agroekowisata di Desa Pasar Rawa. Metode yang dilakukan adalah survei lapangan, sosialisasi, pelatihan menggunakan refraktometer dan penanaman mangrove. Kegiatan sosialisasi dilakukan dengan peserta adalah anggota kelompok LPHD yang berjumlah 27 orang. Dalam presentasi sosialisasi, masyarakat sangat antusias dalam menggali potensi yang ada seperti budaya lokal dan makanan khas daerah tersebut. Pelatihan penggunaan refraktometer dilakukan agar anggota kelompok dapat mengetahui nilai pasti dari rasa manis pada melon dapat dijual dan dijadikan daya tarik bagi wisatawan mencoba melon yang memiliki rasa unik sehingga menjadi nilai jual ekowisata dan agrowisata. Salah satu kegiatan upaya konservasi adalah penanaman mangrove.Kata kunci: agro-ekowisata; hutan mangrove; pemberdayaan masyarakat